Impact of Spark Plasma Sintering Conditions on Ionic Conductivity in La1.95Sr0.05Zr2O7-δ Electrolyte Material for Intermediate Temperature SOFCs. (2nd June 2015) - Huo, Da; Baldinozzi, Gianguido; Siméone, David; Khodja, Hicham; Surble, Suzy
Abstract : To overcome the ageing issues of the solid oxide fuel cells (SOFCs), the proton ceramic fuel cells (PCFCs, also called intermediate temperature SOFCs) technology were developed, which operate at intermediate temperatures (400°-600°C). In this paper, we present the synthesis of Sr-doped lanthanum zirconate pyrochlores La1.95 Sr0.05 Zr2 O7-δ (LSZO) that can be used as electrolyte materials. Conductivity measurements of LSZO were performed in dry and wet (5% H2 O) atmospheres using electrochemical impedance spectroscopy. As the sintering processes are potential to affect not only the bulk conductivity but also the response of grain boundaries, five samples prepared under various SPS conditions were studied.